Cost Constraints as a Malpractice Defense - Morreim, E. Haavi (The Hastings Center report, 1988)
Cost-containment pressures impose fiscal responsibilities upon physicians that can conflict with their fiduciary commitment to patients. Should the law permit health care providers to adjust standards of care according to patients' financial resources? The legal concept of “rebuttable presumption” should be used to reconceive the traditional requirement of a uniform standard of care.